Risk of childhood asthma following prenatal exposure to negative life events and job stressors: A nationwide register-based study in Denmark - Liu, Xiaoqin; Madsen, Kathrine Pape; Sejbaek, Camilla Sandal; Kolstad, Henrik A.; Bonde, Jens Peter E.; Olsen, Jørn; Hougaard, Karin Sørig; Hansen, Kristian Schultz; Andersson, Niklas Worm; Rugulies, Reiner; Schlünssen, Vivi (Scandinavian Journal of Work, Environment & Health, 2019)
' ' OBJECTIVES ': 'This study aimed to examine the association between negative life events, job stressors (low job control or high psychosocial job demands) and offspring asthma phenotypes (early-onset transient, early-onset persistent and late-onset asthma). ' ' METHODS ': 'In a population-based cohort study comprising 547 533 liveborn singletons, we determined negative life events and offspring asthma at age six years using data from Danish nationwide registers. We assessed job demands and job control from gender-specific job exposure matrices. Prevalence ratios (PR) of each asthma phenotype were estimated using log-binomial regression. ' ' RESULTS ': 'Maternal exposure to negative life events prenatally was not significantly associated with offspring asthma. Among mothers with low job demands, low job control was associated with increased risk for early-onset transient asthma [PR=1.14, 95% confidence interval (CI) 1.09–1.19], early-onset persistent asthma (PR=1.17, 95% CI 1.11–1.23), and late-onset asthma (PR=1.06, 95% CI 1.00–1.14). Among mothers with high job demands, low job control was not associated with offspring asthma apart from a reduced risk of early-onset persistent asthma (PR=0.94, 95% CI 0.90–0.97). These associations were independent of child sex and parental atopic history. ' ' CONCLUSIONS ': 'Maternal stressors in private life do not seem to influence offspring asthma significantly. Low job control is associated with offspring asthma, which is modified by maternal psychosocial job demands. Our findings warrant further exploration.
Keywords: asthma; childhood asthma; cohort; cohort study; Denmark; job control; job demand; job stress; job stressor; life event; phenotype; prenatal exposure; register-based study; stress; stressor; work stress